1999
DOI: 10.1590/s0001-37141999000100010
|View full text |Cite
|
Sign up to set email alerts
|

Occorrence of Pseudomicrodochium suttonii in Brazil

Abstract: Pseudomicrodochium suttonii was isolated from the soil of Derby Square, a leisure area in Recife city, Pernambuco, Brazil. For the isolation, suspensions were made in distilled sterile water. According to the literature, this is probably the first occurrence reported in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For example, strains of C. europaea were reported from environmental samples from humid environments (i.e., bathrooms, washing machines) [60], [61], C. reptans was originally isolated from food [24], a strain of C. laciniata was isolated from a bathroom surface, and the ex-type strain of C. oxyspora was isolated from decaying leaf [19]. Cyphellophora suttonii was also detected in soil samples, although this strain has never been sequenced [12]. Other Cyphellophora that have not been involved in human infections are frequently isolated from plants or nutrient-poor substrates, and two species ( C. olivacea and C. oxyspora ) were originally classified in the Phialophora sect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, strains of C. europaea were reported from environmental samples from humid environments (i.e., bathrooms, washing machines) [60], [61], C. reptans was originally isolated from food [24], a strain of C. laciniata was isolated from a bathroom surface, and the ex-type strain of C. oxyspora was isolated from decaying leaf [19]. Cyphellophora suttonii was also detected in soil samples, although this strain has never been sequenced [12]. Other Cyphellophora that have not been involved in human infections are frequently isolated from plants or nutrient-poor substrates, and two species ( C. olivacea and C. oxyspora ) were originally classified in the Phialophora sect.…”
Section: Resultsmentioning
confidence: 99%
“…de Vries [6], encompasses dematiaceous fungi with septate, branched hyphae, intercalary, terminal or lateral phialides with indistinct or funnel-shaped collarettes, and septate, hyaline or pale brown conidia ranging in shape from oblong to fusiform or vermiform. Of the twelve members of the genus described to date, five were isolated samples of animal origin (i.e., nails and skin) [4], [6], [8], [9], [10], [11], whereas the other species occur in soil [12], on plants [13], [14], or as plant endophytes [7], [15]. Based on the analysis of small subunit nuclear ribosomal DNA (nuc18S rDNA) sequences, five species of Cyphellophora formed a strongly supported monophyletic clade that was sister to representatives of the Herpotrichiellaceae [13].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, one new Cyphellophora species, C. chlamydospora, was proposed and C. suttonii is reported for the first time from Europe, isolated from garden soil in Catalonia. The latter species was originally described as an agent of subcutaneous phaeohyphomycosis in a dog in USA (Ajello et al 1980) and was later reported from a human infection in the same country (Perfect and Schell 1996) and from soil in Brazil (Nunes et al 1999). However, the identity of the strains from human and soil have not been confirmed molecularly.…”
Section: Discussionmentioning
confidence: 99%
“…de Vries [6], encompasses dematiaceous fungi with septate, branched hyphae, intercalary, terminal or lateral phialides with indistinct or funnel-shaped collarettes, and septate, hyaline or pale brown conidia ranging in shape from oblong to fusiform or vermiform. Of the twelve members of the genus described to date, five were isolated samples of animal origin (i.e., nails and skin) [4,6,8,9,10,11], whereas the other species occur in soil [12], on plants [13,14], or as plant endophytes [7,15]. Based on the analysis of small subunit nuclear ribosomal DNA (nuc18S rDNA) sequences, five species of Cyphellophora formed a strongly supported monophyletic clade that was sister to representatives of the Herpotrichiellaceae [13].…”
Section: Introductionmentioning
confidence: 99%